Bangladesh Development Update, September 2017 : Towards More, Better, and Inclusive Jobs - World Bank (World Bank, Dhaka, 2017)
The objective of this report is to share perspectives with the Government of Bangladesh, think tanks and researchers, the public as well as the Bank’s senior management on the state of the economy, outlook, risks, progress on structural policy reforms, and key challenges the economy is currently facing. The coverage includes developments in the real sector focusing on poverty, growth, and inflation; external sector developments focusing on the balance of payments, foreign exchange reserves and the exchange rate; fiscal developments focusing on revenue mobilization, public expenditures, and deficit financing; financial sector developments focusing on credit and interest rates; and monetary developments. This update also assesses the progress in Bangladesh’s labor markets and concludes with an exposition of the policy challenges that need to be addressed to accelerate the creation of quality jobs.